1989
DOI: 10.1161/01.hyp.14.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin inhibition of fructose-induced hypertension.

Abstract: The role of insulin resistance and byperinsulinemia in the etiology of fructose-induced hypertension was studied in male Sprague-Dawley rats. Rats consumed a fructose-enriched diet (containing 66% of total calories as fructose) for 11 days and were infused continuously during the last 7 days with either a somatostatin analogue or vehicle. At the end of this period, rats receiving the somatostatin analogue had a lower plasma insulin concentration (52±4 vs. 70±6 /iunits/ml, /><0.01) and a lower blood pressure (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0
3

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(58 citation statements)
references
References 26 publications
3
52
0
3
Order By: Relevance
“…Somatostatin prevents both the hyperinsulinemia and the hypertension in this experimental model. 52 Somatostatin infused over 8 hours has also been reported to decrease arterial pressure (by approximately 14 mm Hg) in obese, hyperinsulinemic hypertensive humans but not in normoinsulinemic hypertensive humans. 51 These findings are intriguing but do not necessarily support the hypothesis that hyperinsulinemia causes hypertension in the presence of insulin resistance.…”
Section: Interaction Of Hyperinsulinemia Insulinmentioning
confidence: 99%
“…Somatostatin prevents both the hyperinsulinemia and the hypertension in this experimental model. 52 Somatostatin infused over 8 hours has also been reported to decrease arterial pressure (by approximately 14 mm Hg) in obese, hyperinsulinemic hypertensive humans but not in normoinsulinemic hypertensive humans. 51 These findings are intriguing but do not necessarily support the hypothesis that hyperinsulinemia causes hypertension in the presence of insulin resistance.…”
Section: Interaction Of Hyperinsulinemia Insulinmentioning
confidence: 99%
“…Hypertension-induced insulin resistance has been demonstrated to accompany increased skeletal muscle vascular resistance (25). Additionally, it has been reported that sucrose feeding increases norepinephrine excretion, turnover, and plasma concentration and enhances sympathetic nerve responses in rats (26,27). Thus sympathetic overactivity may be involved in the pathogenesis of this model, and may be responsible at least in part for the impairment of blood flow to skeletal muscle, which in turn would favor the development of insulin resistance (28).…”
Section: Discussionmentioning
confidence: 99%
“…10 These effects of fructose can be prevented by exercise training 11 or somatostatin. 12 These findings make for a body of cogent experimental evidence, although for the sake of fairness, one should mention that neither SHR nor Dahl rats have been found to be insulin resistant in vivo during euglycemic hyperinsulinemia. 13 3) In schoolchildren surveyed in Bogalusa, Louisiana, both glucose and insulin concentrations predicted higher blood pressure levels, and parental history of diabetes was associated with higher cholesterol.…”
mentioning
confidence: 89%